Impact of menopausal hormone therapy on influenza complications in women: a systematic assessment study - Yu-Hsiang Shih; Chiao-Yu Yang; Chia-Chi Lung (Annals of Medicine)
Background Research on the effects of Menopausal Hormone Therapy (MHT) on influenza outcomes has been limited.Methods This retrospective cohort study utilized data from the TriNetX U.S. Collaborative Network between January 1, 2010, and December 31, 2019, targeting individuals aged 46 to 60 diagnosed with influenza who had not received the influenza vaccination in the prior year. Participants were divided into two cohorts: the MHT cohort, which included individuals who had used estrogen within the preceding 3 months, and the non-MHT cohort, consisting of those who had not used estrogen during the same period. Propensity score matching (PSM) was employed to balance key demographic and clinical variables, including age, race, hypertension, diabetes mellitus, dyslipidemia, pulmonary diseases, and heart diseases. The primary analysis was the assessment of respiratory morbidity within three months following the influenza diagnosis, while secondary analysis included the evaluation of patients with pre-existing lung or heart diseases and those who received antiviral medication.Results After PSM, each cohort included 15,136 women. Women aged 46–60 who used MHT experienced a significant reduction in lung complications, with the risk of influenza pneumonia or respiratory failure decreasing by approximately 40%. However, among patients with chronic conditions such as diabetes, hypertension, hyperlipidemia, lung disease, or heart disease, MHT did not demonstrate a clear protective effect. Similarly, in patients who received antiviral treatment following influenza infection, the MHT group showed no significant reduction in the risk of respiratory complications.Conclusion In conclusion, MHT was associated with a significant reduction in the risk of lung complications in women aged 46–60 without chronic conditions.